2021
DOI: 10.17582/journal.pjz/20200525130507
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism Induces a Positive Selection Pressure at Gag-Pol Sites in Human Immunodeficiency Virus Favoring Drug Resistance Mutations

Abstract: Authors' Contribution AZ conceived, designed and wrote the research article. MAS proofread the study. HJ confirmed the data and sources. MAUK, MN and ARS helped in writing of the article and analysis of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The proportion of URFs among the pol genotyped isolates was significantly higher than Gag. This increased prevalence strikes towards an increased vulnerable hypervirulency in the HIV virus (Zahra et al, 2021).…”
Section: Hiv Genotyping Analysismentioning
confidence: 99%
“…The proportion of URFs among the pol genotyped isolates was significantly higher than Gag. This increased prevalence strikes towards an increased vulnerable hypervirulency in the HIV virus (Zahra et al, 2021).…”
Section: Hiv Genotyping Analysismentioning
confidence: 99%
“…To our knowledge, all PR variants that cause resistance to PI's exhibit dramatically reduced enzyme activity [27][28][29][30]. Many studies have found that cleavage sites in Gag co-evolve with drug resistant mutations in PR, indicating that the mutations in the cleavage sites may compensate for reduced enzyme activity of PR [31][32][33][34][35][36][37][38][39]. Cutsite compensatory evolution has most commonly been associated with the NC/p1 and p1/p6 sites.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] Many studies have found that cleavage sites in Gag coevolve with drug resistant mutations in PR, indicating that the mutations in the cleavage sites may compensate for reduced enzyme activity of PR. [32][33][34][35][36][37][38][39][40] Cut-site compensatory evolution has most commonly been associated with the NC/p1 and p1/p6 sites.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, all PR variants that cause resistance to PI's exhibit dramatically reduced enzyme activity 28–31 . Many studies have found that cleavage sites in Gag co‐evolve with drug resistant mutations in PR, indicating that the mutations in the cleavage sites may compensate for reduced enzyme activity of PR 32–40 . Cut‐site compensatory evolution has most commonly been associated with the NC/p1 and p1/p6 sites.…”
Section: Introductionmentioning
confidence: 99%